PENGARUH ETIKA KERJA TERHADAP DISIPLIN KERJA DAN DAMPAKNYA PADA KINERJA PEGAWAI BALAI PENELITIAN TANAMAN SEREALIA DI KABUPATEN MAROS - Dwiyanto Teguh Purnomo; Maat Pono; Andi Reni (Jurnal Bisnis dan Kewirausahaan, 2023)
The purpose of this study was to determine the effect of work ethics directly on the performance of employees at the Maros Regency Cereals Research Center and to find out that work ethics indirectly influences work discipline on employee performance at the Maros Regency Cereals Research Institute. This study uses the Quantitative Method which aims to explain or measure the relationship or influence, prediction and control based on data obtained from available reports. In this study, the population consisted of all employees working at the Maros Regency Cereal Research Institute, totaling 129 people. The sample was part of the number and characteristics of that population. The sample in this study is all employees with the status of Civil Servants (PNS), namely: 129 people. The results of this study show that the work ethics variable (X) has a direct effect on employee performance variable (Z) of 0.258. While the indirect effect of work ethics (X) on employee performance (Z) through work discipline (Y) has a value of 0.621 x 0.422 = 0.262. From the calculation of the overall effect given by the work ethics variable (X) on employee performance (Z) is a direct effect plus an indirect effect, becoming 0.258 + 0.262 = 0.52.